Mouse Models of Germinal Center Derived B-Cell Lymphomas - Meyer, Stefanie N.; Koul, Sanjay; Pasqualucci, Laura (Frontiers in Immunology, 2021)
Over the last decades, the revolution in DNA sequencing has changed the way we understand the genetics and biology of B-cell lymphomas by uncovering a large number of recurrently mutated genes, whose aberrant function is likely to play an important role in the initiation and/or maintenance of these cancers. Dissecting how the involved genes contribute to the physiology and pathology of germinal center (GC) B cells –the origin of most B-cell lymphomas– will be key to advance our ability to diagnose and treat these patients. Genetically engineered mouse models (GEMM) that faithfully recapitulate lymphoma-associated genetic alterations offer a valuable platform to investigate the pathogenic roles of candidate oncogenes and tumor suppressors in vivo, and to pre-clinically develop new therapeutic principles in the context of an intact tumor immune microenvironment. In this review, we provide a summary of state-of-the art GEMMs obtained by accurately modelling the most common genetic alterations found in human GC B cell malignancies, with a focus on Burkitt lymphoma, follicular lymphoma, and diffuse large B-cell lymphoma, and we discuss how lessons learned from these models can help guide the design of novel therapeutic approaches for this disease.